Investigation of direct and maternal genetic effects on days open in Jersey crossbred cattle - KUMAR, ANSHUMAN; MANDAL, AJOY; GUPTA, A K; VINEETH, M R; RATWAN, POONAM; KARUNAKARAN, M (The Indian Journal of Animal Sciences, 2016)
Estimates of (co)variance and genetic parameters for days open (DO) of Jersey crossbred cattle were estimated by restricted maximum likelihood (REML), fitting 6 animal models, including various combinations of maternal effects. Data on 792 records of 223 Jersey crossbred animals, descended from 51 sires and 170 dams were used. The direct heritability estimates for days open ranged from 0.04 to 0.10 depending on the model applied. The additive maternal effects varied from 0.06 to 0.09 in different models in this study, whereas the estimates of the fraction of variance due to maternal permanent environmental effects were practically negligible to very low (0– 4% of the phenotypic variance), irrespective of the models used. Results suggested that direct and maternal additive effects were important for this trait but, the low heritability estimates indicated little scope of genetic progress through selection for this trait.